Recurrent hepatic artery thrombosis associated with positivity to the anticardiolipin antibody in postoperative liver transplant: Case report and literature review - Ferrer, José Antonio Possatto; Cutovoi, Julia Girardi; Ramos, Anaisa Portes; Ataíde, Elaine Cristina de; Boin, Ilka de Fátima Ferreira (Brazilian Journal of Transplantation, 2013)
Introduction: Hepatic artery thrombosis is a frequent complication following liver transplantation (ranging from 2.0 to 20%), occurring early in 46.7% of cases (30 days after transplant), and requiring re-transplant in about half of cases (53.1%). Antiphospholipid syndrome (APS) is defined as the presence of arterial and/or venous thrombosis associated with antibodies directed to phospholipids. The incidence of APS was estimated in 5 new cases/100000 subjects/year. The occurrence of early hepatic artery thrombosis following transplantation secondary to antiphospholipid syndrome is a rare event. Methods: Case report of a patient undergoing three liver transplants by artery thrombosis associated with anticardiolipin antibody positivity. Results: Male patient, 49 years old, cirrhotic C virus, no thrombotic antecedents, included on the list for liver transplantation by presenting 4.2 cm nodule in liver VI segment in CT scan compatible with Hepatocellular Carcinoma. He underwent liver transplantation under Piggy back technique. In Doppler ultrasound control absence of f low in the hepatic artery, confirmed by angiotomography. Subjected to re-transplant on the 13th postoperative day. After 5 days, patient developed biliary fistula. Performed laparotomy, it was found fistulous orifice with suffering bile duct proximal to the anastomosis of the common bile duct, as well as reduced f low in the hepatic artery with ischemic liver aspect. New computerized tomography did not identify intrahepatic arterial f low, and showed extensive area of hepatic ischemia. It was initiated investigation for thrombophilia, with positive anticardiolipin antibody research. He underwent a third liver transplant, opted by aorto-iliac- hepatic anastomosis with interposition graft of donor iliac artery. Patient showed satisfactory clinical outcome with intra hepatic arterial f low at Doppler control. He was discharged on the 10th postoperative day. Discussion and Conclusion: 33.3% mortality due to early thrombosis of hepatic artery; 7 days of mean diagnostic time; major risk factors (prolonged operative time, low weight of the receiver, mismatch serology for CMV); findings suggest that anticardiolipin is elevated in patients with impaired hepatic function, and may be associated with the pathogenesis of arterial thrombosis although We have not found the use of this drug in patients for treatment and prevent venous thromboembolic events.